311 Radiation-Induced Changes After Stereotactic Radiosurgery for Brain Arteriovenous Malformations: A Systematic Review and Meta-Analysis. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Ilyas, Adeel; Chen, Ching-Jen; Ding, Dale; Buell, Thomas; Raper, Daniel; Lee, Cheng-Chia; Xu, Zhiyuan; Sheehan, Jason P
Abstract: INTRODUCTION: Radiation-induced changes (RICs) are the most common complication of stereotactic radiosurgery (SRS) for brain arteriovenous malformations (AVMs), and they appear as perinidal T2-weighted hyperintensities on magnetic resonance imaging, with or without associated neurological symptoms. The aim of this systematic review and meta-analysis is to determine the rates of RIC after AVM SRS and identify risk factors. METHODS: A literature review was performed using PubMed and MEDLINE to identify studies reporting RIC in AVM patients treated with SRS. RICs were classified as radiologic (any neuroimaging evidence), symptomatic (any associated neurological deterioration, regardless of duration), and permanent (neurological decline without recovery). Baseline, treatment, and outcomes data were extracted for statistical analysis. RESULTS: Based on pooled data from 51 studies, the overall rates of radiologic, symptomatic, and permanent RIC after AVM SRS were 35.5% (1143/3222 patients, 32 studies), 9.2% (499/5447 patients, 46 studies), and 3.8% (202/5272 patients, 39 studies), respectively. Radiological RIC was significantly associated with lack of prior AVM rupture (odds ratio [OR] = 0.57; 95% confidence interval [CI] 0.47-0.69; P  < .001) and treatment with repeat SRS (OR = 6.19; 95% CI 2.42-15.85; P  < .001). Symptomatic RIC was significantly associated with deep AVM location (OR = 0.38; 95% CI 0.21-0.67; P  < .001). CONCLUSION: Approximately 1 in 3 patients with AVMs treated with SRS develop radiologically evident RIC, and of those with radiological RIC, 1 in 4 develop neurological symptoms. Lack of prior AVM hemorrhage and repeat SRS are risk factors for radiologic RIC, and deep nidus location is a risk factor for symptomatic RIC.